IMPLEMENTASI WEBSITE PROMOSI DAN PENJUALAN PADA ASOSIASI PEDAGANG SEPATU DAN TAS KOTA PADANG - Sularno Larno; Muhammad Razi; Putri Anggraini (Prodi Sistem Informasi Universitas Dharma Andalas, 2019)
Association of Bag and Shoes Traders in Padang City has difficulties in the field of data processing for the purchase and sale of goods. Because the processing of this data still uses Microsoft Excel so that to find the necessary files need to be long and also is data redundancy on each file, then an information system is used to provide fast and accurate data. Research conducted directly using interview techniques, then by giving books, literature related to the problems discussed. After the data is collected, the data are grouped and analyzed using the Unified Modeling Language (UML). The results of the analysis are applied in a phpmysql-based data processing information system application program. By designing a new system, making reports related to sales information can be made quickly, precisely and can be solved with errors.